2023
DOI: 10.1371/journal.pone.0284528
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the nomogram to predict the risk of hospital drug shortages: A prediction model

Abstract: Introduction Reasons for drug shortages are multi-factorial, and patients are greatly injured. So we needed to reduce the frequency and risk of drug shortages in hospitals. At present, the risk of drug shortages in medical institutions rarely used prediction models. To this end, we attempted to proactively predict the risk of drug shortages in hospital drug procurement to make further decisions or implement interventions. Objectives The aim of this study is to establish a nomogram to show the risk of drug sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Thus, Tucker and Lee suggested that the problem of drug shortages can only be alleviated by improving stakeholder communication and coordination [ 49 , 50 ]. Liu, Shi, and Dong proposed the need to be proactive instead of reactive by designing different prediction models for drug shortage risk and actively carrying out pre-emptive countermeasures for drug shortage [ 51 53 ]. Tucker proposed a pharmaceutical supply chain model with improvements in terms of configuration, disruption risk, and recovery speed to reduce the probability of drug shortage [ 54 ].…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%
“…Thus, Tucker and Lee suggested that the problem of drug shortages can only be alleviated by improving stakeholder communication and coordination [ 49 , 50 ]. Liu, Shi, and Dong proposed the need to be proactive instead of reactive by designing different prediction models for drug shortage risk and actively carrying out pre-emptive countermeasures for drug shortage [ 51 53 ]. Tucker proposed a pharmaceutical supply chain model with improvements in terms of configuration, disruption risk, and recovery speed to reduce the probability of drug shortage [ 54 ].…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%